Investigation of Low-Level Laser Radiation Effects on Blood Smears Haematological Indices in Breast Carcinoma Patients: Interpretation of Cellular Answers and Clinical Manifestations - Radhi Hussein, Bushra; AL Timimi, Zahra (Asian Pacific Journal of Cancer Biology, 2026)
Background: Low-level laser therapy (LLLT) is able to modulate cellular and immune reactions in clinical conditions. Objective: The purpose of the present investigation was to evaluate the effect of LLLT on blood smear hematological parameters in patients with breast carcinoma. Methods: Red blood cell (RBC) count, white blood cell (WBC) count, hemoglobin content, and platelet count were measured in control and in laser-irradiated samples for different exposure times.” Results: Time-dependent increase in RBC number and hemoglobin was observed, peaking at 1 minute of exposure. WBC and platelet numbers were insignificantly altered. Morphological examination, on the other hand, revealed the increased percentage of reactive lymphocytes, indicating immune cell activation. Conclusion: The results suggest that LLLT influences cellular shape but not leukocyte numbers to a great extent, suggesting potential immunomodulatory effects that warrant further investigation in vivo.